Genome-wide association identifies a common variant in the reelin gene that increases the risk of schizophrenia only in women. - Sagiv Shifman; Martina Johannesson; Michal Bronstein; Sam X Chen; David A Collier; Nicholas J Craddock; Kenneth S Kendler; Tao Li; Michael O'Donovan; F Anthony O'Neill; Michael J Owen; Dermot Walsh; et al. (PLoS Genetics)
Sex differences in schizophrenia are well known, but their genetic basis has not been identified. We performed a genome-wide association scan for schizophrenia in an Ashkenazi Jewish population using DNA pooling. We found a female-specific association with rs7341475, a SNP in the fourth intron of the reelin (RELN) gene (p = 2.9 x 10(-5) in women), with a significant gene-sex effect (p = 1.8 x 10(-4)). We studied rs7341475 in four additional populations, totaling 2,274 cases and 4,401 controls. A significant effect was observed only in women, replicating the initial result (p = 2.1 x 10(-3) in women; p = 4.2 x 10(-3) for gene-sex interaction). Based on all populations the estimated relative risk of women carrying the common genotype is 1.58 (p = 8.8 x 10(-7); p = 1.6 x 10(-5) for gene-sex interaction). The female-specific association between RELN and schizophrenia is one of the few examples of a replicated sex-specific genetic association in any disease.